Scientific foundations of education - Weiss, Thomas M.; Hoover, Kenneth H. (Dubuque : W.C. Brown Co. Publisher, 1960)
This book concerns the scientific foundations of education. It has been developed with the hope that those who study it seriously will be in a better position to understand their own motivations in education, and the motivations of others who are involved with the school and its activities.
Part I. Education, science, and philosophy -- Part II. Social problems of education -- Part III. Professional, history, and aims of education.
Includes bibliographical references and index.
Keywords: EDUCATION